Habitus and Symbolic Violence in Sar Culture, Merauke, Papua - Hallatu, Trinovianto George Reinhard; Wisadirana, Darsono; Mu'adi, Sholih; Chawa, Anif Fatma (JSW (Jurnal Sosiologi Walisongo), 2021)
The sar culture is the pre-existing culture of the Kanum tribe whose implementation is aimed to maintain and preserve nature. Sar culture not only has a positive influence on the environment, but it also represents symbolic violence against women and the Kanum people. This research is aimed to describe sar culture based on the theory of habitus and symbolic violence by Bourdieu. This research involved a qualitative descriptive method, in which the data was obtained from in-depth interviews with Kanum tribal head, Kanum tribe elders, and some village residents involved in sar, observation in Naukenjerai district, and supported by literature review. All collected data were then analyzed descriptively according to the concepts of habitus and symbolic violence by Bourdieu. The research results show that sar culture is a habitus resulting from an interaction between human beings and their nature that has existed for long before. Besides that, there is symbolic violence to the Kanum women and also to the Kaum people, which done by the Kanum men and the leaders of the Kanum tribe as the dominant actors.